2018
DOI: 10.1264/jsme2.me17144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Rhizobium</i> Species Living with the Dark Septate Endophytic Fungus <i>Veronaeopsis simplex</i> on Organic Substrate Utilization by the Host

Abstract: Bacteria harbored in/on the hyphae of the dark septate endophyte, Veronaeopsis simplex Y34, were identified as a single Rhizobium species by molecular analyses of bacterial 16S rRNA genes, and were successfully isolated from the endophyte. The Rhizobium-cured fungus was prepared thoroughly by an antibiotic treatment, thereby allowing an examination of their effects on organic substrate utilization. Assays with Biolog® FF microplates revealed that the respiration potential for 52.6% of the tested compounds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Community level physiological profiles (CLPP) are most commonly analyzed by the Biolog ® (29) and MicroResp ™ methods (17). The Biolog ® method is a rapid analysis (36, 63), although only a fraction of the microbiome is analyzed due to soil extraction before the reaction. Furthermore, selective carbon sources may change bacterial community structures during the incubation period.…”
mentioning
confidence: 99%
“…Community level physiological profiles (CLPP) are most commonly analyzed by the Biolog ® (29) and MicroResp ™ methods (17). The Biolog ® method is a rapid analysis (36, 63), although only a fraction of the microbiome is analyzed due to soil extraction before the reaction. Furthermore, selective carbon sources may change bacterial community structures during the incubation period.…”
mentioning
confidence: 99%
“…Fungi-bacteria interactions ( e.g ., Rhizobium sp.-endophytic fungi, soil indigenous bacteria-pathogenic Fusarium sp., and Burkholderiaceae- related endobacteria and plant and soil fungi Mortierella spp.) related to plant growth and health were also investigated (8, 26, 44). Mourad et al .…”
mentioning
confidence: 99%
“…Microbial symbioses are ubiquitous in nature ( 53 ); from protists to humans, all plants and animals are inhabited by microbes that comprise the majority of global biodiversity ( 6 ). In the past two decades, an increasing number of studies have shown that many plant-associated fungi, including foliar ascomycetes ( 1 ), dark septate endophytes (DSEs) ( 18 ), arbuscular mycorrhizal fungi (AMF) ( 4 , 47 ), ectomycorrhizal basidiomycetes ( 3 , 19 ), and sebacinalean endophytes ( 40 ), as well as a few phytopathogenic fungi ( 27 , 31 ) and neutral fungi living in soil ecosystems ( 30 , 37 , 39 , 51 ), harbor phylogenetically diverse bacteria in both epihyphal and endohyphal forms. These bacteria are affiliated to Alpha- , Beta- , Gammaproteobacteria , Mollicutes , Bacillaceae , Chitinophaga , and others, and are known to alter host morphology, sporulation, metabolite production, and even other properties involved in interactions with plants ( 16 , 36 , 41 , 49 ).…”
mentioning
confidence: 99%
“…Another noteworthy plant-beneficial fungal group is DSEs, intimately associated with symbiotic bacteria ( 18 ). DSEs are defined as conidial or sterile ascomycetous fungi that colonize the root tissues of diverse plants intracellularly and intercellularly without any harmful effects or typical mycorrhizal structure formation ( 2 , 23 , 29 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation